1998
DOI: 10.1034/j.1600-0420.1998.760522.x
|View full text |Cite
|
Sign up to set email alerts
|

Iris retraction syndrome associated with nonrhegmatogenous retinal detachment

Abstract: ABSTRACT.Purpose: To present the first documentation of iris retraction syndrome in eyes with nonrhegmatogenous retinal detachment. Patients and Methods: One patient with age-related macular degeneration and another with panuveitis developed exudative retinal detachment with iris retraction configuration. Ultrasound biomicroscopy was performed to investigate the anatomic relationship of structures in the anterior segment of the eye. Results: Ultrasound biomicroscopy demonstrated a severe backward bowing of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Geyer is the only other author to report IRS in patients without RD; however, IRS in his patients resolved with pupillary dilation, while bilateral iris retraction in our patient persisted with dilation, as seen in Fig. 2 [ 17 ].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Geyer is the only other author to report IRS in patients without RD; however, IRS in his patients resolved with pupillary dilation, while bilateral iris retraction in our patient persisted with dilation, as seen in Fig. 2 [ 17 ].…”
Section: Discussionmentioning
confidence: 64%
“…Mechanical traction on anterior structures was proposed by Jarret when he noted PVR in eyes with a posteriorly bowing iris following RD [ 26 ]. The term “iris retraction syndrome” was not coined until 1984, and both Cambell’s original explanation and Geyer’s subsequent amendment in 1998 require hypotony as a key physiological step [ 17 , 27 ]. In summary, all documented cases of posterior iris bowing from Schnaubel in 1876 to Geyer in 1998 occur in the setting of hypotony due to either rhegmatogenous RD or ciliary body shutdown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our patient's visual acuity remained 20/200, despite successful retinal detachment repair and management of iris retraction. Campbell demonstrated how iris retraction and iris bombé can be associated, by noting the conversion to iris retraction with the administration of aqueous suppressants to his patients with iris bombé and return to iris bombé again when the medication was stopped [ 6 ]. Given this, laser peripheral iridotomy should be considered in patients with IRS to prevent subsequent episodes of angle closure glaucoma, as occurred in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…In 1984, Campbell [ 5 ] was the first to name the condition IRS and proposed the most commonly accepted mechanism for the condition, in which seclusion of the pupil and egress of subretinal fluid are the drivers of iris retraction. However, debate remains regarding the mechanism of fluid egress that leads to hypotony, as Geyer et al [ 6 ] reported 2 cases of IRS associated with nonrhegmatogenous retinal detachment. In 1996, Morinelli et al [ 7 ] demonstrated with ultrasonography the characteristic anterior chamber appearance of IRS.…”
Section: Introductionmentioning
confidence: 99%